Why Do Employees Want to Resign? Investigating Factors Influencing Turnover Intention: Evidence from the Beverage Company in Thailand - Ponchaitiwat, Khwanruedee; Wannatham, Sanisa; Kokanuch, Anchalee (Journal of Multidisciplinary in Social Sciences, 2025)
This study examines how work enjoyment, the physical work environment, compensation and benefits, coworker support, supervisor support, and career growth opportunities influence employee turnover intention in the Thai beverage industry. Data were collected from 117 employees, and multiple regression analysis was used to test the hypotheses. The findings show that only compensation and benefits, as well as supervisor support, have significant negative effects on turnover intention. Interestingly, career growth opportunities were positively associated with turnover intention. These results suggest the need for organizations to align compensation practices and supervisory support with employee expectations in order to reduce turnover. The study offers insights into employee attitudes and their implications for organizational commitment, and it also outlines directions for future research.